m6A: An Emerging Role in Programmed Cell Death - Tang, Fajuan; Chen, Lin; Gao, Hu; Xiao, Dongqiong; Li, Xihong (Frontiers in Cell and Developmental Biology, 2022)
Programmed cell death is an active extinction process, including autophagy, ferroptosis, pyroptosis, apoptosis, and necroptosis. m6A is a reversible RNA modification which undergoes methylation under the action of methylases (writers), and is demethylated under the action of demethylases (erasers). The RNA base site at which m6A is modified is recognized by specialized enzymes (readers) which regulate downstream RNA translation, decay, and stability. m6A affects many aspects of mRNA metabolism, and also plays an important role in promoting the maturation of miRNA, the translation and degradation of circRNA, and the stability of lncRNA. The regulatory factors including writers, erasers and readers promote or inhibit programmed cell death via up-regulating or down-regulating downstream targets in a m6A-dependent manner to participate in the process of disease. In this review, we summarize the functions of m6A with particular reference to its role in programmed cell death.